Mubi-Toram lexicon and Afro-Asiatic IV: Addenda with *b- (Part 2) - Takács, Gábor (Lingua Posnaniensis, 2023)
The paper is another part of a planned longer series designed to step by step reveal the Chadic and wider Afro-Asiatic cognate heritage in the lexical stock of the Mubi-Toram languages which represent the easternmost (26th) group of the vaste Chadic (i.e., 6th) branch of the gigantic Afro-Asiatic family.